Strategic human resource management in health care - Fottler, Myron D.; Khatri, Naresh; Savage, Grant T. 1954- (Advances in health care management ;, 2010)
Strategic management of HR in health care is important in delivering high-quality patient care. Given that salary and wages constitute about 65 to 80% of the total operating budget in a typical health care organization and also the fact that people play a critical role in delivering high quality patient care, it is imperative for health care organizations to manage their human resources more effectively. Unfortunately, the HR function remains one of the most neglected in health care organizations and 'warm body syndrome' seems to characterize the role of HRM in health care organizations. The purpose of the special issue of AHCM on Human Resource Management is to explore the strategic role that HR function can play in delivering high quality and affordable health care.